Travelah / Zadlan Fikre Ismail ... [et al.] - Ismail, Zadlan Fikre; Mohamed Salim, Neesa Ameera; Shawalludin, Syahrini (Universiti Teknologi MARA, Kedah, 2020)
Travelah is a smart phone application meant for travelers in Malaysia. Travelah provideservices for local and international travelers to explore the beauty of Malaysia. Travelah offers numerous packages including hotel packages, transport rentals, exploring historical places packages, and exploring local food and cuisine. Travelers will be offered affordable packages and guidance throughout their travelling experience. Travelah is a Malaysias travel app which has everything a traveler need to explore the amazing Malaysia!